Lao People's Democratic Republic : Joint Staff Advisory Note of the Poverty Reduction Strategy Paper. (IMF Staff Country Reports; Country Report ;, 2004)
The Joint Staff Advisory Note (JSAN) of the Poverty Reduction Strategy Paper Progress Report for the Lao People's Democratic Republic (PDR) reviews the strengths and weaknesses of poverty reduction objectives and strategies. The Lao PDR National Growth and Poverty Eradication Strategy (NGPES) is the first full poverty reduction strategy prepared by the government. The NGPES describes the participatory process underpinning the development of the strategy. Capacity constraints, weak governance, and a difficulty translating strategic objectives into concrete actions are the main obstacles to the reform process.